Preventative Pretrial Detention and the Failure of Interest-Balancing Approaches to Due Process - Alschuler, Albert W. (1986)
This article, echoing Highmore's treatise of 1783, maintains that neither a legitimate nor a very important governmental interest can justify preventive detention in the absence of significant proof of past wrongdoing or an inability to control one's behavior. Both the Supreme Court's neglect of this issue and Congress' similar neglect in the preventive detention provisions of the Federal Bail Reform Act of 1984 reveal the extent to which cost-benefit analysis has captured American law and threatened core concepts of individual dignity. The article does not oppose all forms of preventive pretrial detention. To the contrary, it recognizes that the detention without bond of a person accused of crime can be consistent with Anglo-American legal tradition, with fundamental fairness, and with sound policy. The article maintains, however, that the Federal Bail Reform Act of 1984 is unconstitutional in failing to require adequate preliminary proof of guilt or convictability as a predicate for extended detention. The Act disregards concepts of individual freedom and responsibility that have dominated the law of pretrial detention from the time of Bracton. After describing the 1984 Act, the article offers a historical retrospective on due process adjudication. It emphasizes the differences between fundamental fairness and interest-balancing approaches to the due process clause. Turning specifically to Schall v. Martin, it examines the two-tiered interest-balancing formula employed in that case, a formula declaring that intrusions upon fundamental personal interests are consistent with due process so long as they sufficiently advance compelling governmental interests - and that restrictions of nonfundamental individual interests are constitutional when they adequately further legitimate governmental interests. The article contends that this familiar framework is deeply flawed. In some contexts, it is too activist; in others, too restrained. The article rejects several broad-gauged objections to all forms of preventive pretrial detention - their asserted dependency on an unattainable ability to predict human behavior, their asserted incompatibility with the historic goals of pretrial detention, and their asserted departure from the presumption of innocence. The article also maintains that no persuasive constitutional challenge can be mounted to the Bail Reform Act of 1984 (or, indeed, to substantially more intrusive preventive detention measures) under current interest-balancing due process formulas